STUDY OF THE CONCEPT OF MOVEMENT DYNAMICS BASED ON ETHNOPHYSICS IN THE TANGGAI DANCE - Putri Zasa Aslamiya; Apit Fathurohman; Esti Susiloningsih (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
Culture in Indonesia is known to be very diverse, which has not been explored to its full potential due to limited access and minimal awareness of resources in preserving it. Physics learning is often still teacher centered with students becoming uncertain and feeling bored because they think this learning is only based on formulas. So local wisdom is needed with physics learning to implement the concept of movement dynamics with an ethnophysical approach by involving phenomena in students' daily lives to more easily understand learning. Regional dances are one of the local wisdoms that have direct contact with students at school, one of which is the Palembang regional dance, namely the Tanggai dance. This research aims to identify studies of the concept of movement dynamics in movements in the Tanggai Palembang dance. This type of research uses descriptive qualitative with a documentation study approach and the object of this research is the Tanggai dance. Data was collected using two methods, namely the training video analysis method and literature study and the observation method. The results of the research were a study of the concept of movement dynamics in each movement of the Tanggai Palembang dance, especially on the material of Newton's law when changing positions in each movement, moments of force and circular motion in rotating hand swings, conditions for equilibrium of rigid bodies, frictional forces on the legs when walking, and changes in points dancer weight. The ethnophysical approach has the potential to be an innovation in physics learning because it is able to train students scientific literacy to think critically through culture that is integrated into knowledge.